Environmental Hazards and Neurodevelopment 2015
DOI: 10.1201/b18030-17
|View full text |Cite
|
Sign up to set email alerts
|

B-Lymphocytes from a Population of Children with Autism Spectrum Disorder and Their Unaffected Siblings Exhibit Hypersensitivity to Thimerosal

Abstract: The role of thimerosal containing vaccines in the development of autism spectrum disorder (ASD) has been an area of intense debate, as has the presence of mercury dental amalgams and fish ingestion by pregnant mothers. We studied the effects of thimerosal on cell proliferation and mitochondrial function from B-lymphocytes taken from individuals with autism, their nonautistic twins, and their nontwin siblings. Eleven families were examined and compared to matched controls. B-cells were grown with increasing lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Three cross‐sectional studies assessed different endpoints relevant to neurotoxicity in children. One of them was a large cross‐sectional study from the C8 cohort (Stein and Savitz, ) which showed a statistically significant association between serum PFHxS and diagnosis of ADHD (based on interview, including medications) in children and adolescents. Same‐direction non‐statistically significant associations between were also reported for PFNA (and PFOS).…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Three cross‐sectional studies assessed different endpoints relevant to neurotoxicity in children. One of them was a large cross‐sectional study from the C8 cohort (Stein and Savitz, ) which showed a statistically significant association between serum PFHxS and diagnosis of ADHD (based on interview, including medications) in children and adolescents. Same‐direction non‐statistically significant associations between were also reported for PFNA (and PFOS).…”
Section: Assessmentmentioning
confidence: 99%
“…Associations between PFASs and Attention Deficit Hyperactivity Disorder (ADHD) and learning problems in children were investigated by Stein and Savitz (). This was a cross‐sectional study in the C8 cohort exposed to PFOA from contaminated drinking water.…”
Section: Appendix J – Human Observationsmentioning
confidence: 99%
“…Indeed, a positive association between PFAS exposure and several neurological traits such as impulsivity ( 83 ), attention-deficit/hyperactivity disorder (ADHD) ( 84 , 85 ), behavioral problems ( 86 ), or poorer executive function ( 87 ) was reported by some epidemiological studies. However, these findings were in most cases not confirmed by longitudinal studies, reporting no association between ADHD ( 88 , 89 ), autism spectrum disorders ( 88 , 90 , 91 ), parent- or teacher-reported behavioral scores ( 86 , 92 , 93 ), or cognitive abilities ( 94 , 95 ) of exposed children.…”
Section: Prenatal Exposure To Pfas: Effects On Maternal and Neonatal mentioning
confidence: 99%
“…When researchers identified health risks such as high cholesterol or dangerously poor organ function, the C8 Study could be credited for saving lives (Lyons 2007). The C8 Study produced 38 articles 4 on the relationship between PFOA exposure and health outcomes, including hyperactivity (Stein and Savitz 2011), liver function (Gallo et al 2012), pregnancy outcomes (Savitz et al 2012;Stein, Savitz, and Dougan 2009), and thyroid function (Lopez-Espinosa et al 2012). Furthermore, the C8 Science Panel identified significant associations between PFOA exposure and kidney cancer, testicular cancer, ulcerative colitis, thyroid disease, pregnancy-induced hypertension, and hypercholesterolemia (C8 Science Panel 2011, 2012a, 2012b, 2012c, 2012d.…”
Section: The C8 Health Projectmentioning
confidence: 99%